Legal Analysis of the Role of Autopsy in Revealing the Crime of Murder Based on the Criminal Code - Risdalina, Risdalina; Kumalasari M, Indra; Tampubolon, Lorent (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The purpose of this study is to find out and understand the Role of Autopsy in Revealing a Murder Crime and the obstacles faced by investigators in the autopsy process in revealing a Murder crime. This study uses a normative legal research type. Discussion Results: First, Forensic Autopsy has a very important role in revealing a Murder crime. The results of a forensic autopsy in the Criminal Procedure Code (KUHAP) are used as evidence either in the form of expert testimony and/or letters (visum et repertum). The results of a forensic autopsy clearly have a legal basis, this is clearly regulated in the Criminal Procedure Code. The forensic autopsy process is very important in identifying the cause and effect of a person's death. So that forensic autopsy evidence has a clear legal position in the Criminal Procedure Code as evidence either in the form of expert testimony and/or letters; second, the obstacles faced by investigators in conducting an autopsy in revealing a Murder crime include: The victim's family objects, Lack of competent investigator human resources, Lack of experienced experts.